Zhongguo fu nü zhuan ji ci dian : er shi shi ji juan (1912-2000) - Stefanowska, A. D.; Lee, Lily Xiao Hong; Wiles, Sue, 1940- (Sydney da xue chu ban she, 2016)
Though many works on the achievements of Chinese people exist, women rarely feature. This volume contains over 300 biographies of Chinese women including foreigners with significance in China. The book features revolutionaries, activists, novelists, poets, scientists, lawyers and many other significant women of the twentieth century."--JSTOR website (viewed April 10, 2017).